3D Volumetric Evaluation of Lipiodol Retention in HCC after Chemoembolization: A Quantitative Comparison between CBCT and MDCT - Wang, Zhijun (2014)
RATIONALE AND OBJECTIVES: To evaluate the capability of cone-beam computed tomography (CBCT) acquired immediately after transcatheter arterial chemoembolization (TACE) in determining Lipiodol retention quantitatively and volumetrically when compared to 1-day post-procedure unenhanced MDCT. MATERIALS AND METHODS: From June to December, 2012, fifteen patients met the inclusion criteria of unresectable hepatocellular carcinoma (HCC) that was treated with conventional TACE (cTACE), and had intra-procedural CBCT and 1-day post-TACE MDCT. Four patients were excluded because the Lipiodol was diffuse throughout the entire liver or Lipiodol deposition was not clear on both CBCT and MDCT. Eleven patients with a total of 31 target lesions were included in the analysis. A quantitative and 3D software was used to assess complete, localized and diffuse lipiodol deposition. Tumor volume, Lipiodol volume in the tumor, % Lipiodol retention, and Lipiodol enhancement in Hounsfield Unit (HU) were calculated and compared between CBCT and MDCT using two-tailed student’s t-test and Bland-Altman plots. RESULTS: The mean value of tumor volume, Lipiodol deposited regions, calculated average % Lipiodol retention, and HU value of CBCT were not significantly different from those of MDCT (tumor volume: 9.37±11.35cm3 vs. 9.34±11.44cm3, P=0.991; Lipiodol volume: 7.84±9.34cm(3) vs. 7.84±9.60 cm(3), P=0.998; % Lipiodol retention: 89.3%±14.7% vs. 90.2% ± 14.9%, P=0.811; HU value: 307.7±160.1 HU vs. 257.2±120.0 HU, P=0.139). Bland-Altman plots showed only minimal difference and high agreement when comparing CBCT to MDCT. CONCLUSION: CBCT has a similar capability, intraprocedurally, to assess Lipiodol deposition in 3D for patients with HCC treated with cTACE when compared to MDCT.